Manifestations of women in the constitution and (re)presentation of the feminist political subject - López-Cespedes, Sharon (2023)
This article is part of the research project Ni una Menos, Costa Rica, Manifestations and representations of women in the constitution and (re)presentation of the feminist political subject, during 2019 and 2021. This includes the main findings of a series of interviews that were carried out with Costa Rican feminist activist women, collectively organized, and its goal is to draw some characterizations of the contemporary feminist subjects, from their feelings, thoughts, and actions in the fight against gender violence. Thus, we explore collectives’ organizational origins, their articulation and political organization, as well as their scope and challenges